ESTIMATION OF LAND SURFACE TEMPERATURE USING LANDSAT TM THERMAL INFRARED IN SELANGOR-NEGERI SEMBILAN - Asmala, A.; Noorazuan, H.; Buang, Zolkepli (Universiti Teknikal Malaysia Melaka, 2006)
A full-scene of Landsat TM acquired on April 17, 1988 (path 127/row58) was used in this study. This scene covers the areas of Selangor and north part of Negeri Sembilan in Peninsular Malaysia. The main objective of this study is to evaluate the use of remote sensed information, especially thermal band 6 to gain land surface temperature (LST) using thermal band of Landsat images. The result will be compared with urban and non-urban surfaces by using normalised difference vegetation index (NDVI) and compare relationships between them. The initial result showed that the correlation between the LST and the NDVI over ten locations in the study area is quite significant. The derivation of LST map using remote sensing technique in this study is useful in providing information for analysing geophysical parameters over Selangor-Negeri Sembilan area, especially dealing with the urban heat island phenomenon.